THE EFFECT OF THE INSIDE AND OUTSIDE THE CIRCLE STRATEGY ON PHYSICAL SELF AND THE LEARNING OF OVERHEAD PASSING AND DRIBBLING SKILLS IN HANDBALL FOR STUDENTS - Saleh, Ali Abdul-Hussein Hamoud (Indonesian Journal of Sport Science and Technology (IJST), 2025)
Technical qualities as well as a sound body awareness are important for learning handball successfully. However, the common instructional method has tended to concentrate students' performance results rather than their self-perception and learning engagement. This study thus sought to alleviate this lack by focusing on the impacts of Inside-and-Outside-the-Circle Strategy over students’ physical self-concept and their learning of overhead pass as well as dribbling skills in handball. The research used an experimental approach to 60, randomly sampled, 17-year-old high-school students who were assigned with a pretreatment posttest control group design. Inside-and-Outside-the-Circle Strategy on experimentation, and the common teaching method was used in the control group. These students (pre and post-tested) data analysis was done by SPSS to determine the significant at p ≤ 0.05 for each variable. Participants in either condition showed positive outcomes, but those of the intervention group gained more (statistically significant improvement) in all variables. These findings indicate that the Inside and Outside the Circle Strategy places physical self and motor skill learning more effectively than does traditional approach. This method of training also provides a new way of encouraging self-efficacy and motivational involvement in handball learning. The findings add to physical education pedagogy by providing evidence that engaging students in movement-based interactive activities can be used as a tool for enhancing psychomotor and affective learning.